Pengaruh Kemudahan dan Harga Produk Online di Shopee Terhadap Perubahan Gaya Hidup Konsumtif Mahasiswa Universitas Teuku Umar - Fadhillah, Risa; Chairunnisa, Cut; Marwan; Abdul Manan, Afni (Teewan Journal Solutions, 2025)
This study analyzes the effect of ease of use and product prices in the Shopee application on the consumer behavior of students of the Faculty of Economics, Teuku Umar University. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that neither ease of use (X1) nor product price (X2) had a significant effect on consumer behavior (Y), with significance values ​​of 0.419 and 0.283, respectively (p> 0.05). The coefficient of determination (R Square) shows that only 5.8% of the variation in consumer behavior can be explained by these two variables, while the rest is influenced by other factors.